Contrastive and Error Analysis - Siti Ismahani; Yusriani Y; Syafira S; Sonia Sabilla; Nurasiah Anggini; Anis Syafa Wani (Educare: Journal Educational and Multimedia, 2025)
Contrastive analysis and error analysis in understanding the challenges faced by Indonesian students in learning English. Using a qualitative approach, this study analyzes data on errors made by students in the use of tenses , vocabulary, and pronunciation, which are influenced by interference from Indonesian. Data were collected through English tests and interviews with students, then analyzed using the contrastive and error analysis framework. The results show that the main difficulties faced by students lie in the differences in tense structures , errors in vocabulary selection, and pronunciation difficulties influenced by the phonetic habits of Indonesian. This study suggests that English teaching needs to focus more on the structural differences between the two languages and provide intensive practice to correct frequent errors..